Hubungan Keletihan Ibu Nifas Dengan Motivasi Menyusui Di Wilayah Kerja Puskesmas Gebang Kabupaten Langkat - Meily Siburian; Joiseva Pardosi; Dorma Silaban; Askinah Askinah; Lasria Simamora (Pusat Riset dan Inovasi Nasional, 2023)
Behavior about clean and healthy living in educational institutions is an effort to empower students, teachers and the community in the school environment to know, want to do and be able to practice a set of behaviors on the basis of awareness as learning outcomes, so that they are independently able to prevent disease, improve their health, and play an active role in creating a healthy environment . Behavior regarding clean and healthy living is an indicator of achievement in improving health in the 2015-2030 Sustainable Development Goals (SDGs) program. In the SDGs, behavior regarding clean and healthy living is one of the prevention strategies with short-term impacts for improving health in regional settings, namely schools, families and communities. During the COVID-19 pandemic, school-age children and adolescents were at risk of contracting COVID-19 due to their high activity and tendency to group. However, due to their good immune system, often COVID-19 in this group shows no symptoms or only mild symptoms, so they are often ignored and have the potential to spread to people around them. The impact of COVID-19 on school-age children and adolescents can affect their physical and mental health. Based on the description above, the authors conducted research on the effect of implementing UKS activities on Clean and Healthy Behavior. This research is a quantitative research with a correlation study design with the type of research used is Analytical Observational. The research was conducted at Middle School 2 Kualuh Leidong, North Labuhan Batu Regency, North Sumatra Province in March -May 2022 with a sample size of 70 respondents. Sampling in this study used a probability sampling technique with proportional stratified sampling. Data analysis in this study includes Univariate and Bivariate Analysis with the provision that if ρ ≤ α 0.05 then there is an influence or relationship between the two variables. The results of the study obtained a p value of 0.000 which means that there is an influence of the School Health Business program on Clean and Healthy Behavior. It is hoped that the puskesmas staff will socialize the school health program and activity plan, complete facilities that support clean and healthy behavior and further increase school involvement and collaboration with parties related to the implementation of activity programs or clean and healthy living in the working area of the Tanjung Leidong community health center.